Factors affecting treatment, management and mortality in cases of retroperitoneal hematoma after cardiac catheterization: a single-center experience - Gündeş, Ebubekir; Aday, Ulaş; Bulut, Mustafa; Çiyiltepe, Hüseyin; Çetin, Durmuş Ali; Gülmez, Selçuk; Senger, Aziz; Değer, Kamuran Cumhur; Polat, Erdal; Duman, Mustafa (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2017)
Introduction: There is little information available on the clinical aspects, results, treatment and management of cardiac catheterization-related retroperitoneal hematoma. Data on the subject are rather limited, and current publications are based on a limited number of retrospective cohort studies and case reports. Aim : To perform a retrospective analysis of the demographic, clinical, and in-hospital results of patients who developed retroperitoneal hematoma (RPH) after cardiac catheterization (CC). Material and methods: The cases of 124,064 patients who had CCs between January 2010 and October 2016 were retrospectively analyzed. Patients diagnosed with RPH were classified into three groups depending on the method of treatment: conservative (group 1), endovascular stenting (group 2), and surgery (group 3). The independent risk factors, based on RPH-related mortality, were determined by logistic regression analysis. Results: Of the 68 (0.054%) patients with RPH, 75% received conservative treatment, 13.2% underwent angiographic stent placement, and 11.7% had surgical treatment. Red blood cell packets (RBCPs) (p = 0.043), duration of hospitalization (p = 0.007), and mortality rates (p = 0.006) were statistically significantly higher in group 3 in comparison to the other groups. Multivariate subgroup analysis was conducted to determine mortality rates, with post-procedural highest creatinine ≥ 2 mg/dl and RBCPs ≥ 10 established as independent risk factors. Conclusions : Hemodynamically stable patients with no active hemorrhaging are shown to have good results with conservative treatment. We believe that endovascular methods should be used initially for hemodynamically unstable patients, while surgical treatment should be employed in cases where endovascular methods fail or abdominal compartment syndrome develops.